In-Vitro Evaluation Of Novel Synthetic Compounds Against Fusarium Sacchari - VINOD KUMAR SEWARIYA; RICHA SHRIVASTAVA; GBKS PRASAD; KISHOR ARORA (International Journal of Pharma and Bio Sciences, 2012)
A total of seven Pyrazolones and Pyridines and three Schiff bases were evaluated in-vitro against Fusarium sacchari, the causative organism of wilt disease of sugarcane. The pyridine based compounds were found superior to pyrazolone compounds. Two compounds viz., 3-methyl-1-Phenyl-5-pyrazolone (C5) and 2-Benzyl Pyridine (C10) recorded significant anti-microbial activity against Fusarium sacchari in- vitro.